A Cobalt-based Nanostructured Electrode Prepared by a Fast Chemical Method - Alhebshi, Nuha A. (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
The demand for nanomaterials is rapidly increasing in most applications, such as energy storage devices. Many nanomaterial synthesis methods are energy-consuming methods requiring high temperatures, prolonged reaction time, complicated steps, or expensive equipment. Herein, nanostructures of cobalt hydroxide chloride, Co2(OH)3Cl, have been directly deposited on carbon cloth microfibers by a fast and simple step of chemical bath deposition. Co2(OH)3Cl nanoparticles appear in only 10 minutes of the deposition time, then the nanoflakes are grown in 60 minutes, as imaged by scanning electron microscope. The crystal structure of Co2(OH)3Cl is characterized using X-ray diffraction, while the results of energy-dispersive X-ray spectroscopy confirm the elemental analysis. The electrochemical energy storage mechanism of Co2(OH)3Cl electrode in potassium hydroxide electrolyte depends on the semi-reversible redox reactions as investigated by the cyclic voltammetry and by the galvanostatic charge-discharge measurements. As a result, the prepared electrode in 60 min exhibits a maximum specific capacitance of 313 F/g versus 293 F/g for the prepared electrode in 10 min, both at 1 A/g. The good electrochemical performance is attributed to several features, including the nanoflakes morphology that enables electrolyte ions to penetrate the electrode freely, the well-crystallized structure, and the solid electronic path between the current collector and the active material indicated by the Nyquist plot of electrochemical impedance spectroscopy. Our cost-effective synthesis of cobalt hydroxide chloride nanostructures on woven substrates offers flexible binder-free electrodes in alkaline electrolytes. This research opens up the potential for these materials to be used as a power source in smart textiles and wearable electronics, thereby contributing to the advancement of these fields.